الادب في التصور الاسلامي - Zulhannan Zulhannan (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2010)
The article explores the scientific references containing literary concepts in Islamic perspectives, including its characteristics and criteria. The references are the expression of life values that relate to human beings and universe. In this case, Islam provides several guidelines that should be followed in order to achieve the sustainability of human beings and universe life.